Model Perilaku Konsumsi Lintas Generasi dalam Bertransaksi Digital - Afni Sirait; Ida Ayu Purnama; Crescentiano Agung Wicaksono (Universitas Medan Area, 2021)
Changes in people's consumption styles and trends today are fundamentally influenced by the use of technology. The COVID-19 pandemic is one of the tearing points that explains that technology is a basic need today. Digital transactions are familiar and even greet all generations. This study aims to analyze the consumption behavior model of each generation hierarchy in digital transactions. Respondents from this study were generations X, Y, and Z, each of which consisted of 50 respondents. Data analysis method using Path Analysis using WarmPLS 6.0 statistical software. The results of data processing show that there is no direct or indirect relationship from cultural factors to the desire to transact digitally for generations X, Y, and Z although it is mediated by consumption behavior variables. Psychological factors influence generations Y and Z in digitally transacting fully mediated by consumption behavior variables. This study provides additional knowledge about behavioral models that influence and motivate the three generations in digital transactions.